Implementasi Khotaman Al-Quran dalam Membentuk Karakter Religius IPNU IPPNU Desa Bekiring - Shokhifah, Eka Zahrotu; Susanto, Hanafi Hadi (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The formation of the Banom or IPNU IPPNU organization in Bekiring village, Pulung sub-district, Ponorogo, already has one of the programs, namely Al-Quran khotaman. The aim of this research is to describe the habituation of religious activities in forming religious character. The service method used is Asset Based Community Development (ABCD). Data collection techniques use observation, interviews and documentation. Because character education itself is a behavioral education that is formed through habitual action or habits and exemplary, to form the character itself there must be habituation that must be done. With the Khotaman Al-Qur'an activity, it is hoped that it will be able to provide understanding to youth and the community in Bekiring Village, Pulung District, to continue reading the Koran and be able to strengthen faith. The program is to make khotamil Qur'an activities as a medium of da'wah which aims to deepen religious knowledge and also to strengthen the IPNU IPPNU membership forum in Bekiring village, Pulung sub-district.